DIGITAL ECONOMY: ERA OF INNOVATION AND CHANGE (International Journal of Innovative Technologies in Economy, 2023)
In the rapid development of information technologies and digital platforms, the digital economy profoundly impacts all spheres of public life. This study constitutes a profound analysis of the development of the digital economy within the context of contemporary innovative transformations. The author aims to identify key aspects of the era of digital changes, assessing their influence on the business environment and societal relations. The objective of the study is a systematic exploration of the main trends and dynamics of the digital economy, with a focus on innovative changes and the identification of prospective development directions in this field. The research concentrates on analyzing structural changes and strategic shifts occurring within the digital economy, delving into key components such as digital technologies, innovative business models, and the social aspects of digital transformation. The study employs methods of systemic analysis, literature review, and the analysis of theoretical ideas in this domain. The foundation of the research lies in the analysis of existing theoretical concepts and practical cases of implementing digital innovations. The results of the study provide strategic recommendations for enterprises and public structures aiming at the effective utilization of digital technologies. The practical significance of the work lies in identifying key success factors in the era of digital changes. This study presents a comprehensive perspective on the evolution of the digital economy, offering evidence-based conclusions and recommendations for all stakeholders focused on achieving success in the modern digital world.